(untitled) (American Journal of Technology and Applied Sciences, 2023)
The article discusses the main essential characteristics of pop vocal art in the context of the specifics of pop-jazz performance. The focus is on musical style, performing traditions, acoustic features of the singer’s voice, the physiology of the impact of pop-jazz singing on listeners, the main tasks of the educational process aimed at mastering it.